Genetic Diversity Among Puntius Sophore Complex Using Restriction Fragment Length Polymorphism - Balaraj, Smitha (Richtmann Publishing, 2012)
Restriction Fragment Length Polymorphism (RFLP) analysis of genomic DNA was employed to characterize species ofPuntius sophore complex, a benthopelagic freshwater fish species. Samples of five species of Puntius viz, Puntius sophore, Puntiusamphibius, Puntius chola, Puntius bimaculatus and Puntius dorsalis from the east flowing Tamiraparani and Kuzhithurai and west flowingTamiraparani river basins (Western Ghats) were analyzed. The restriction enzyme employed (Hind III) generated species-specific DNApatterns for each of the five species. DNA exhibited considerable polymorphism among species. All samples showed relatively highvalues of diversity. The relation between species is discussed.